Soil Fungi in an Over-burned Tropical Rain Forest in Bukit Bangkirai, East Kalimantan - SUCIATMIH SUCIATMIH (Biodiversitas Journal of Biological Diversity, 2006)
A study was conducted in Bukit Bangkirai forest, East Kalimantan, to understand the impact of forest fire on the existence of soil fungi. Three permanent plots were used for the research, i.e. undamaged plot (K), lightly damaged plot (LD), and heavily damaged plot (HD). Each plot was 1 ha and divided into 100 sub-plots (10 m x 10 m). For observation of soil fungi, in the center of the five randomly selected sub-plots from each plot was made a sampling plot (2 m x 2 m). After removing the organic matter surface (O layer), soil sample was collected from top layer (A) and second layer (B) in each of the five sampling plots. Soil fungi were isolated using dilution plate method and they were incubated at room temperature (27-28 oC). This process was replicated two times for each soil sample. The result indicated that forest fire decreased the diversity and population of soil fungi. The highest soil fungi population was found in the undamaged (K) plot at the top layer (A) (389.0 colonies/mg dry soil), while the lowest population was in the lightly damaged plot (LD) at the second layer (B) (12.3 colonies/mg dry soil). Gongronella butleri was dominant species in the area of the tropical rain forest which was fired in Bukit Bangkirai, East Kalimantan. Â© 2006 Jurusan Biologi FMIPA UNS Surakarta Key words: damaged and undamaged plots, colony, population, soil fungi, soil layer